Improvement of the Process Stability of Arylmalonate Decarboxylase by Immobilization for Biocatalytic Profen Synthesis - Aßmann, Miriam; Mügge, Carolin; Gaßmeyer, Sarah Katharina; Enoki, Junichi; Hilterhaus, Lutz; Kourist, Robert; Liese, Andreas; Kara, Selin (Frontiers in Microbiology, 2017)
The enzyme arylmalonate decarboxylase (AMDase) enables the selective synthesis of enantiopure (S)-arylpropinates in a simple single-step decarboxylation of dicarboxylic acid precursors. However, the poor enzyme stability with a half-life time of about 1.2 h under process conditions is a serious limitation of the productivity, which results in a need for high catalyst loads. By immobilization on an amino C2 acrylate carrier the operational stability of the (S)-selective AMDase variant G74C/M159L/C188G/V43I/A125P/V156L was increased to a half-life of about 8.6 days, which represents a 158-fold improvement. Further optimization was achieved by simple immobilization of the cell lysate to eliminate the cost- and time intensive enzyme purification step.